2021
DOI: 10.5829/ijee.2021.12.03.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mixing Rate on Performance of Anaerobic Reactor in Methane Production

Abstract: In this study, a mathematical model was used to predict the dynamic behaviour of the system under conditions of imperfect mixing in an Anaerobic Digestion (AD) process. To evaluate the system performance, the effect of mixing parameters by calculating the quantities of methane gas produced, system power, and effluent quality was investigated. Numerical results showed that with an increase in the mixing rate ( ) by 20%, methane production rate, power production, and the effluent COD removal efficiency of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been reported that biomethane production increased by 220% with 160 rpm bidirectional mixing [48]. Mixing may be profcient by employing hydraulic (liquid recirculation), mechanical (manually or using a mixer), and pneumatic (recirculation of gases) systems at various frequencies (continuously or intermittently several times in an hour during a day) and strengths (intermittent, gentle, and rotation speed) [49].…”
Section: Agitation/mixingmentioning
confidence: 99%
“…It has been reported that biomethane production increased by 220% with 160 rpm bidirectional mixing [48]. Mixing may be profcient by employing hydraulic (liquid recirculation), mechanical (manually or using a mixer), and pneumatic (recirculation of gases) systems at various frequencies (continuously or intermittently several times in an hour during a day) and strengths (intermittent, gentle, and rotation speed) [49].…”
Section: Agitation/mixingmentioning
confidence: 99%
“…A proper mixing leads to uniformity of materials and temperature in wastewater and causes the efficient material transfer from substrate to microorganisms in the large volume of the reactor [3]. According to investigations, methane gas production rate and the effluent quality using anaerobic digesters are significantly affected by the mixing [4,5].…”
Section: Introductionmentioning
confidence: 99%